Visual function at school age in children with neonatal encephalopathy and low Apgar scores. Issue 3 (21st April 2004) - Mercuri, E; Anker, S; Guzzetta, A; Barnett, A L; Haataja, L; Rutherford, M; Cowan, F; Dubowitz, L; Braddick, O; Atkinson, J
Abstract : Objective: To assess different aspects of visual function at school age in children who suffered from neonatal encephalopathy. Method: Thirty nine full term infants with neonatal encephalopathy, low Apgar scores, and early neonatal imaging were studied using a battery of tests assessing different aspects of visual function (crowding acuity, stereopsis, visual fields) at school age. The results were compared with brain magnetic resonance imaging (MRI) findings and, when possible, with the results of the assessment of visual function performed at 5 and 12 months, available in 24 of the 39 children examined at school age. Results: Sixteen of the 39 children (41%) had abnormal results at school age in at least one of the visual tests used. Seven of these 16 were untestable on all tests. The remaining 23 children (59%) had normal results. Conclusions: The presence and severity of visual impairment was related to the severity of brain lesions. Moderate or severe basal ganglia lesions and severe white matter changes were always associated with abnormal visual function. Infants with normal MRI, minimal basal ganglia lesions, and minimal or moderate white matter involvement tended to have normal vision. It was also found that the assessment of visual function performed in the first year was a reliable indicator of visual function at school age. With two exceptions, the results on the 5 month visual assessment were predictive of visual outcome at school age. In the remaining two cases, a normal visual outcome at 5 years was associated with visual abnormalities at 5 months but these had already normalised by the age of 1 year.